An investigation into the claim that free fee higher education in South Africa would be regressive - Nana, Vitesh (My University, 2017)
The South African higher education student protests which began in October 2015 have culminated in the student body voicing increased demands for the implementation of free fee higher education. Key policy stakeholders and commentators have been critical of this demand stating that such a policy would be regressive and ‘destructive’ due to the fact that the rich dominate the student cohort, the net result of which would be the poor funding the higher education of the rich. There is a continued emphasis on the private benefits that higher education provides graduates, therbey necessitating tuition fees. This paper has shown that these arguments, dating back to the 1970s, have weak theoretical foundations. The view that the rich dominate the student cohort is questioned with the finding that only 18% of the households containing students are classified as rich. As the rich provide 97% of personal income tax revenue and 76% of value added tax revenue it would be difficult for the poor to fund the rich. The states ‘chronic underfunding’ of the higher education system comes amid ‘budgetary pressures’ highlighting the continued adherence of the state to fiscal austerity measures. These austerity measures have increasingly shifted the financial burden of higher education onto students. A financial burden that 80% of households are deemed to require financial assistance to meet. In reducing state funding to the higher education system, in real terms, the private benefits of higher education are used to lure students into paying ever increasing tuition fees, even taking on debt in order to do so.
Thesis (M.Com. (Development Theory and Policy))--University of the Witwatersrand, Faculty of Commerce, Law and Management, School of Economic and Business Sciences, 2017
Keywords: Education, Higher--South Africa--Finance; Education, Higher--Economic aspects--South Africa